Post-Viral Pain, Fatigue, and Sleep Disturbance Syndromes: Current Knowledge and Future Directions - Caleb Tackey; P. Maxwell Slepian; Hance Clarke; Nimish Mittal (Canadian Journal of Pain, 2023)
ABSTRACTBackground Post-viral pain syndrome, also known as post-viral syndrome, is a complex condition characterized by persistent pain, fatigue, musculoskeletal pain, neuropathic pain, neurocognitive difficulties, and sleep disturbances that can occur after an individual has recovered from a viral infection.Aims This narrative review provides a summary of the sequelae of post-viral syndromes, viral agents that cause it, and the pathophysiology, treatment, and future considerations for research and targeted therapies.Methods Medline, PubMed, and Embase databases were used to search for studies on viruses associated with post-viral syndrome.Conclusion Much remains unknown regarding the pathophysiology of post-viral syndromes, and few studies have provided a comprehensive summary of the condition, agents that cause it, and successful treatment modalities. With the COVID-19 pandemic continuing to affect millions of people worldwide, the need for an understanding of the etiology of post-viral illness and how to help individuals cope with the sequalae is paramount.